PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 136 PEKANBARU - Nia Purnama; Hendri Marhadi; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to improve the learning outcomes of IPS with the application of cooperative learning model type course review horay (CRH) class VC SD Negeri 136 Pekanbaru. The low student learning outcomes can be caused by improper learning models. This problem is often encountered in learning with many concepts, there by increasing the activity of remembering the students, one of them is on social science learning and the teacher does not optimize the learning media to make students quickly bored. This study uses a classroom action research design consisting of two cycles and four stages of planning, implementation, observation and reflection. Student learning outcomes have improved after the application of cooperative learning model of course review horay (CRH) type, can be seen from the average score on score score 68,71 increase on the first cycle of 79.61 and on the second cycle of 90,51. With the increase of learning outcomes in the first cycle of 15.86% and on the second cycle of 31.71%. These results prove that the application of cooperative learning model type course review horay (CRH) can improve the learning outcomes of students in grade V in Elementery School.Keywords: Cooperative course horay review type (CRH), IPS learning result